1980
DOI: 10.1002/jss.400140212
|View full text |Cite
|
Sign up to set email alerts
|

Plate‐Induced tumors of BALB/3T3 cells exhibiting foci of differentiation into pericytes, chondrocytes, and fibroblasts

Abstract: The BALB/3T3 clone A31 mouse embryo cell line has been used by many investigators as a model "normal" "fibroblast" line for a variety in vitro studies. It has been shown, however, that these cells are not "normal" because they will produce tumors within 2-4 months if 3 x 10(4) cells are implanted subcutaneously in BALB/c mice attached to 0.2 x 5 x 10-mm plastic plates. Previous studies also suggested that these cells were not fibroblasts because they gave rise tumors with the characteristics of vascular endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The data in Table VII list these mitogens. They include epidermal growth factor, phorbol myristate acetate, methyl isobutyl xanthine, 30% fetal calf serum, and a cyst fluid, designated TuGF, which was derived from tumors induced by implantation of BALB/c 3T3 cells on plastic plates into syngeneic mice (4,15).…”
Section: R E I N I T I a T I O N O F C E L L P R O L I F E R A T I O Nmentioning
confidence: 99%
“…The data in Table VII list these mitogens. They include epidermal growth factor, phorbol myristate acetate, methyl isobutyl xanthine, 30% fetal calf serum, and a cyst fluid, designated TuGF, which was derived from tumors induced by implantation of BALB/c 3T3 cells on plastic plates into syngeneic mice (4,15).…”
Section: R E I N I T I a T I O N O F C E L L P R O L I F E R A T I O Nmentioning
confidence: 99%
“…We found that constitutive downregulation of dlk in BALB/c 3T3 cells increases their adipocyte differentiation in response to insulin. BALB/c 3T3 are cells of mesenchymal origin with a differentiation potential similar to that of bone marrow stromal cells (4,35). We therefore used these cells as stroma for in vitro growth of pre-B cells.…”
mentioning
confidence: 99%
“…Tumorigenicity Fox et al, 1977: Fox et al, 1976, 1977Wetzel et al, 1977;Tucker et al, 1977Barker and Sanford, 1970Sanford et al, 1972Aaronson and Todaro, 1968Boone and Scott, 1980Aaronson and Todaro, 1968 Boone (Boone and Jacobs, 1976). It, too, may therefore be considered preneoplastic.…”
mentioning
confidence: 99%